A tutorial for electronic circuit design using spice. - Escoto, Miguel T. Jr.
A general approach to electronic circuit design is outlined. The iterative design path is identified to cite, particularly, the usefulness and the advantages of circuit simulation. Finally, a design example for a high voltage DC power supply is developed. Applying Spice demonstrates the usefulness of circuit simulation in the iterative process of circuit design before the circuit is built and after one thinks the design is complete.